Soil quality status under Hazton’s paddy farming: A case study in Banyumas Regency, Indonesia - Supriyadi, Supriyadi; Ustiatik, Reni; Mukti, Brilliant; Minardi, Slamet; Widijanto, Hery; Sakti, Muchammad Bima Gegana (Universitas Sebelas Maret, 2022)
Soil quality is the ability of the soil to perform its function, such as providing nourishment to the plants. However, intensive paddy farming, such as Hazton’s paddy farming method, is suspected to deteriorate soil quality status and degrade land sustainability. This study aimed to analyze soil quality under Hazton’s paddy farming. This study was conducted on paddy fields in Banyumas Regency using a randomized block design with treatment consisting of 1) conventional method as a control, 2) Hazton’s method + organic fertilizer, 3) Hazton’s method + organic fertilizer + decomposer, and 4) Hazton’s method + organic fertilizer + decomposer + leaf fertilizer. Soil quality was determined according to a minimum data set (MDS) that consisted of organic C, pH, total N, available phosphorus (P) and potassium (K), base saturation (BS), cation exchange capacity (CEC), bacterial density, soil respiration, and C/N ratio. The MDS was scored and calculated using the soil quality index formula and then classified from very low to very high (<0.19-1). This study highlighted that the soil quality in paddy farm using Hazton’s method in Banyumas Regency ranged from low (0.444) to very low (0.308). The application of organic fertilizer is not sufficient enough to refill the nutrient pool equal to harvested plant biomass. This leads to soil quality deterioration and affects land sustainability. Therefore, yield and biomass production should be included as soil quality indicators in future studies. Additionally, further soil degradation can be avoided by continuously assessing soil quality and the necessary conservation measures for preventing and minimizing further land degradation can be applied.